Effects of multicomponent training on the intrinsic capacity of community-dwelling older adults: quasi-experimental study protocol - Sarah Giulia Bandeira Felipe; Clarissa Biehl Printes; Fabiane de Oliveira Brauner; Douglas Kazutoshi Sato; Rafael Reimann Baptista (Brazilian Society of Geriatrics and Gerontology, 2024)
Objective: This is a protocol for assessing the effects of multicomponent exercise on the intrinsic capacity of older adults. Methods: Older adults (≥ 60 years old) will be selected for a multicomponent training program in Porto Alegre, RS, Brazil to evaluate the 5 domains of intrinsic capacity: vitality (handgrip strength, body mass index, and nutrition) sensory perception (self-reported questions), psychology (the 15-item Geriatric Depression Scale), cognition (the Montreal Cognitive Assessment) and locomotion (the sit-to-stand test and the Timed Up and Go test). The composite intrinsic capacity score will be obtained by summing the domains, with total scores ranging from 0 to 10 points. After 12 weeks of the multicomponent exercise intervention, the participants will be reassessed. Student's t-test and ANOVA will be used to compare the effects of different types of training on intrinsic capacity. This study was approved by the research ethics committee of the involved institution. Expected results: After the 12-week multicomponent exercise intervention, we expect scores for composite intrinsic capacity and its domains, especially locomotion, to increase. Relevance: The risk of dependence, falls, and mortality increases with reduced intrinsic capacity, indicating a need for interventions to limit these negative outcomes. Multicomponent exercise, a simple, widely recommended, and effective strategy with good adherence, is designed to prevent intrinsic capacity decline in older people and improve their health and functionality.